Polyvinylidene fluoride-added ceramic powder composite near-field electrospinned piezoelectric fiber-based low-frequency dynamic sensors - Pan, Cheng-Tang (2021)
In this study, near-field electrospinning (NFES) is used to fabricate BaxSr1–xTiO3 (BST)/poly(vinylidene fluoride) (PVDF) piezoelectric fiber composites with excellent mechanical properties and chemical properties. BST ceramic powder is blended with PVDF solution uniformly to prepare a solution of appropriate conductance. The parameter for BST/PVDF fiber processing is based on PVDF fibers. Scanning electron microscopy, differential scanning calorimetry, microtensile testing, Fourier transform infrared spectroscopy, and electricity test of the blends of BST/PVDF fibers are incorporated. Mechanical properties of the fibers are then measured by microtensile testing. Effects of distinct ratios of Ba/Sr and the content of Ba0.7Sr0.3TiO3 ceramic powder on BST/PVDF piezoelectric fibers are discussed. Finally, BST/PVDF piezoelectric fiber composites are patterned on a poly(ethylene terephthalate) (PET)-based structure with an interdigital electrode as a BST/PVDF flexible energy harvester to capture ambient energy. The results show that the BST ceramic powder is ∼58–93 nm, and the diameters of piezoelectric fiber composites are ∼6.8–13.7 μm. The tensile strength of piezoelectric fiber composites is ∼74.92 MPa, and the Young’s coefficient tensile strength is ∼3.74 GPa. Mechanical properties are 2–3 times higher than those of pure PVDF piezoelectric fibers. The maximum open-circuit voltage and closed-loop current of BST/PVDF fibers reached ∼1025 mV and ∼391 nA, respectively. The electromechanical energy conversion efficiency of the BST/PVDF energy harvester is found to be 1–2 times higher than that of the PVDF energy harvester. It is confirmed and validated that the addition of BST ceramic powder could effectively increase the piezoelectric constant of PVDF piezoelectric fibers.